Equitable estoppel and restitution as interstitial causes of action - McFarlane, B (Oxford University Press, 2024)
This chapter considers the function, form, and limits of two causes of action: equitable estoppel and the restitutionary claim exemplified by the case of a mistaken payment. It is argued that each cause of action plays the same interstitial role: it supplements (but does not correct) primary legal rules, such as those of contract and property, which endow parties with legal powers. By mitigating some of the practical problems that can arise from the existence of such powers, each cause of action deals with problems which the law itself creates. This analysis helps us to understand the limits on the doctrines and shows that each has a characteristically equitable function.